(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Haemophilia is the most frequent diagnosed inborn clotting factor deficiency in newborn. Studies reveal that majority of hemophilia A cases are due to an inversion of the long arm of X-chromosome. Newborns with hemophilia are at risk of intracranial and extracranial hemorrhage, and other bleeding complications. Diagnostic criteria for haemophilia include confirmation of a factor activity level below 40% of normal (below 0.40 IU/mL), or a hemophilia gene mutation. Haemophilia typically result in an isolated prolongation of the activated partial thromboplastin time. However, the definitive diagnosis requires measurement of factors VIII and IX levels. Here, we describe a newborn with cephalhematoma gastrointestinal bleeding that is the manifestation of neonatal haemophilia with antenatally diagnosed duodenal atresia and there is no positive family history. This case shows a rare hemophilia presentation reflecting the importance of coagulation studies when faced with unexplained bleeding.